Analisis Tingkat Kecemasan Matematika Siswa Kelas VII MTs Negeri 2 Sidoarjo pada Materi Kesebangunan Ditinjau Berdasarkan Gender - Safira, Natasya Putri; Yanti, Aning Wida; Kurniawan, Agus Prasetyo (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to describe the level of mathematics anxiety among seventh-grade students in class VII-A at MTs Negeri 2 Sidoarjo when learning about similarity, viewed from the perspective of gender differences. This study used a quantitative descriptive research design with 32 students as subjects, consisting of 16 male students and 16 female students. Data were collected through a mathematics anxiety questionnaire containing 30 statements covering three aspects, namely cognitive, affective, and physiological. The results showed that the overall level of mathematics anxiety was high, with an average score of 84.34. When viewed by aspect, student anxiety was in the moderate category for the cognitive aspect (27.85), high for the affective aspect (32.16), and moderate for the physiological aspect (21.73). Based on gender, female students had a higher level of anxiety (average score of 84.81) than male students (average score of 83.87). These findings indicate that gender differences affect the level of mathematics anxiety, with female students tending to experience more emotional and physical anxiety when facing mathematics lessons than male students.